2008
DOI: 10.1016/j.neurobiolaging.2006.10.031
|View full text |Cite
|
Sign up to set email alerts
|

I. Longitudinal changes in aging brain function

Abstract: Changes in brain activity over time were evaluated in a group of older adults in the Baltimore Longitudinal Study of Aging who maintained good physical and cognitive health. Participants underwent PET scans during rest and delayed verbal and figural recognition memory performance at Year 1 baseline and at Year 9. While memory performance remained stable over the 8 years, longitudinal changes in regional cerebral blood flow were observed within each scan condition. Further analyses revealed distinctive patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 74 publications
(79 reference statements)
8
54
0
1
Order By: Relevance
“…Changes in the patterns of brain activity, including both increased and decreased rCBF, are seen when comparing the older brain to the young brain 12,13 and are observed over time in healthy older subjects as they age. 14,15 In the present study, HTN is associated with greater longitudinal decline in middle and inferior prefrontal regions, the anterior cingulate gyrus, occipitotemporal regions, and in visual association cortices relative to HCs. Our HTN subjects also show regions where blood flow patterns do not indicate relative increases over time to the same extent as HC.…”
Section: Pet Findingssupporting
confidence: 48%
“…Changes in the patterns of brain activity, including both increased and decreased rCBF, are seen when comparing the older brain to the young brain 12,13 and are observed over time in healthy older subjects as they age. 14,15 In the present study, HTN is associated with greater longitudinal decline in middle and inferior prefrontal regions, the anterior cingulate gyrus, occipitotemporal regions, and in visual association cortices relative to HCs. Our HTN subjects also show regions where blood flow patterns do not indicate relative increases over time to the same extent as HC.…”
Section: Pet Findingssupporting
confidence: 48%
“…the older) males. However, this method of calculation does not reflect the fact that absolute or whole-brain values were actually higher in paired and lesioned males than in the lone males (F 2 = 4.99, p = 0.027), an effect that is opposite to that you would expect based on normal changes in brain metabolism with age reported in the human imaging literature (Martin et al, 1991;Takada et al, 1992;Burns and Tyrrell, 1992;Zuendorf et al, 2003;Beason-Held et al, 2006;Kalpouzos et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
“…Although cross-sectional studies are easier to carry out, and have contributed most of what we know to date about aging of the brain, they are vulnerable to cohort effects, and longitudinal studies are necessary for identifying the effects of aging within individuals. There have been a few longitudinal studies of brain function in older adults, which have shown decreased task-related activity over time 193 , both decreases and increases, depending on the specific brain region and cognitive demands 194,195 , and a greater decline of activity in older individuals with risk factors for AD 196 . With so few data points it is difficult to come to any strong conclusions about change over time, highlighting the need for these kinds of studies.…”
Section: Discussionmentioning
confidence: 99%